Evaluation of a newly isolated thermophilic microalga Chlorella sorokiniana UNM-IND1 as biodiesel feedstocks - NUR ZAKIYAH RAMADANI; INDRAYANI INDRAYANI; ELMI NURHAIDAH ZAINUDDIN (Society for Indonesian Biodiversity, 2024)
Abstract. Ramadani NZ, Indrayani, Zainuddin EN. 2024. Evaluation of a newly isolated thermophilic microalga Chlorella sorokiniana UNM-IND1 as biodiesel feedstocks. Biodiversitas 25: 3339-3349. Microalgae contain lipids and fatty acids that can be used as an alternative energy for biodiesel. Efforts to increase lipid productivity in microalgae can be done by conditioning the microalgae under certain stress conditions. Temperature is one of the environmental factors that can stimulate lipid production in microalgae. This study aims to analyze the effect of different temperatures on the growth, biomass, lipid productivity and fatty acid composition of a newly isolated microalgae Chlorella sorokiniana Shihira & Krauss, 1965 UNM-IND1 and to evaluate the potential of the microalga as biodiesel feedstocks. The C. sorokiniana UNM-IND1 was initially cultured at three different temperature conditions namely culture room temperature (25-26°C), ambient room temperature (28-32°C) and drying room temperature (32-48°C) (phase I). In phase II, the cultures were transferred to lower temperature conditions and incubated for 3 days. The parameters measured were cell density, specific growth rate, biomass productivity, lipid content, lipid productivity and fatty acid composition. The results showed that all cultures can grow at all culture conditions tested. The highest specific growth rate and biomass productivity were achieved at drying room temperature treatment at 0.790 d-1 and 0,166 g.L-1.d-1, respectively. The highest lipid productivity (0.0674 g.L-1.d-1) was obtained at culture room temperature. After the temperature shift, the lipid yield, lipid content and lipid productivity of all cultures increased. Fatty acid analysis showed that the alga consists of mainly palmitic acid, linolenic acid and linoleic acid. Based on the growth, biomass, lipid and fatty acid composition, the C. sorokiniana UNM-IND1 has potential as a biodiesel feedstock.